PENGGUNAAN ALAT PERAGA DENGAN PEMBELAJARAN LANGSUNG DALAM MENINGKATKAN MOTIVASI MENGAJAR GURU DI SMPN 2 KUBU KABUPATEN ROKAN HILIR - Baharuddin (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This study aimed to determine whether the use of instructional props in direct instruction could enhance teachers’ motivation to teach at SMP Negeri 2 Kubu, Rokan Hilir Regency. The research question addressed in this study was whether the use of instructional props could increase teachers’ teaching motivation at SMP Negeri 2 Kubu. The study focused on improving teacher motivation in teaching through the use of instructional props. The research was conducted at SMP Negeri 2 Kubu, Rokan Hilir Regency, with 18 teachers serving as the research subjects. The teachers had heterogeneous levels of motivation and had not intensively used instructional props during the learning process. Based on the analysis and discussion of the data, it can be concluded that the use of instructional props effectively improved teachers’ motivation to teach. This was indicated by improvements in several aspects. In the first cycle, the principal’s role as a facilitator achieved a score of 25, equivalent to 63% of the assessed activity indicators. In the second cycle, this score increased significantly to 38, representing 95% achievement of all assessed aspects. In terms of teacher participation, in the first cycle, the score obtained from the implementation of the principal’s directives was 73, with an achievement percentage of 51%. In the second cycle, the level of participation increased to 74%, with a score of 106, indicating higher engagement compared to the first cycle. Furthermore, teachers’ teaching motivation in using instructional props showed a consistent increase. In the first cycle, the motivation level reached 64%, categorized as good, while in the second cycle it increased to 88%, categorized as very good. These findings indicate that the use of instructional props in direct learning effectively enhances teachers’ motivation to teach at SMP Negeri 2 Kubu, Rokan Hilir Regency.